Legalitas Perlindungan Hukum Haji Furoda: Studi Kasus Haji Tahun 2025 - Muntafi, Ahmad Zaki (Indonesian Journal Publisher, 2025)
This study examines the legal protection of Furoda Hajj pilgrims in 2025, particularly in light of the failure to issue the mujamalah visa, which is a prerequisite for the implementation of this non-quota pilgrimage program. The Furoda Hajj, carried out through official invitations from the Saudi Arabian government, operates outside Indonesia’s regular quota, creating a unique legal position for the pilgrims involved. The purpose of this research is to analyze the extent of legal protection available to pilgrims who fail to depart and to assess the government’s responsibility in safeguarding their rights. Employing a normative juridical approach, this study relies on statutory and conceptual analysis of laws, regulations, and governance practices related to Hajj administration. The findings reveal that although the Furoda Hajj is legally acknowledged, its legal protection remains uncertain, as statutory responsibility is limited to the regular Hajj quota. This gap has significant implications, particularly regarding the supervision, transparency, and accountability of organizers, as well as the refund of funds paid by pilgrims. In conclusion, the non-issuance of mujamalah visas in 2025 highlights the urgent need for regulatory reforms and stronger state involvement to ensure that Furoda Hajj pilgrims receive fair legal protection, security, and justice in line with public expectations.